2013
DOI: 10.4161/auto.23814
|View full text |Cite
|
Sign up to set email alerts
|

LC3 fluorescent puncta in autophagosomes or in protein aggregates can be distinguished by FRAP analysis in living cells

Abstract: LC3 is a marker protein that is involved in the formation of autophagosomes and autolysosomes, which are usually characterized and monitored by fluorescence microscopy using fluorescent protein-tagged LC3 probes (FP-LC3). FP-LC3 and even endogenous LC3 can also be incorporated into intracellular protein aggregates in an autophagy-independent manner. However, the dynamic process of LC3 associated with autophagosomes and autolysosomes or protein aggregates in living cells remains unclear. Here, we explored the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 55 publications
2
30
0
Order By: Relevance
“…Recent studies suggested that LC3 is the first protein recruited to the autophagosome membrane. The conversion of the soluble form LC3-I to the autophagic vesicle-associated form LC3-II is considered a specific marker of autophagosomes promotion 26, 27. To assess MHY2256-induced autophgic cell death, Western blot analysis and acridine orange staining were performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies suggested that LC3 is the first protein recruited to the autophagosome membrane. The conversion of the soluble form LC3-I to the autophagic vesicle-associated form LC3-II is considered a specific marker of autophagosomes promotion 26, 27. To assess MHY2256-induced autophgic cell death, Western blot analysis and acridine orange staining were performed.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies also reported inhibition of cell growth in various types of cancer by a few different SIRT inhibitors 27, 28. Most researchers have described the antitumor effects of SIRT inhibitors in cancer cells, which are closely attributed to the activation of p53 31, 32.…”
Section: Discussionmentioning
confidence: 98%
“…[38][39][40][41] To measure FRET between Cerulean-and Venus-tagged versions of LC3 and SQSTM1, we used acceptor photobleaching, a well-characterized method to quantify energy transfer by fluorescence microscopy. 14,[42][43][44][45][46][47] In our experiments, we measured FRET between Cerulean-SQSTM1 and the various Venus-LC3 constructs separately for the diffuse cytoplasmic pool of the proteins and in puncta ( Fig. 3).…”
Section: Sqstm1 and Lc3 Are In Close Physical Proximity In The Cytoplmentioning
confidence: 99%
“…12 These experiments thus measure the diffusional mobility of soluble pools of LC3 and SQSTM1, as opposed to turnover of the 2 proteins on puncta. 44 Using the Stokes-Einstein equation, it is possible to estimate the apparent molecular weight of the soluble complexes associated with each protein assuming a spherical geometry (D »MW ¡1/3 , with Venus as a standard for MW). 12,14 As a starting point, we measured D for cytoplasmic Venus, which should diffuse as a monomer with an expected molecular mass of »27 kDa, and should not form a complex with SQSTM1.…”
Section: Lc3 Forms a Large Complex With Overexpressed Sqstm1 As Measmentioning
confidence: 99%
“…There was a small proportion (less than 20%) of CLB that did contain some by inhibiting autophagy and the UPS (Wang et al, 2013). However, there was a higher frequency of CLB with wild-type LC3-GFP (51%) than the mutated form (less than 20%), indicating that the presence of LC3-GFP in CLB is related to autophagic function.…”
Section: Autophagy Components Are Found In Clbmentioning
confidence: 94%